A Qualitative Case Study on the Attitude of Surf Retail Stores Towards the Use of Environmentally Friendly Packaging in Muizenberg, Cape Town - Robb, Brandon (The IIE, 2020)
Businesses’ plastic production for packaging is increasing around the world each year as these plastics are made for single use packaging with some of it ending up in the oceans. The research study aims to determine the attitudes of Muizenberg’s surf retail stores towards the use of environmentally friendly packaging. The implementation of environmentally friendly packaging by these surf retail stores and the extent to which they use this form of packaging are also considered as research objectives. The study makes use of a case study, limiting the data to surf retail stores who are based in Muizenberg, Cape Town enabling the researcher to remain focussed on smaller samples. Qualitative questionnaires were used as a data collection tool to understand the participants unique experiences. The researcher monitored the completion of the questionnaire within an online meeting. The participants included store owners and managers of the surfing retail stores. A thematic analysis was used to organise the collected data into various developed themes related to answering the research question. The main theme identified within the study was the positive emotions and feelings the surf retail stores had towards environmentally friendly packaging. The research findings indicated that surfing retail stores had a positive attitude towards environmentally friendly packaging and did in fact implement the use of it to a large extent. The study contributes towards creating awareness for the use of environmentally friendly packaging; however, it was limited to Muizenberg and can be expanded to larger areas.
Keywords: Environmentally friendly packaging; Attitudes; Surfing; Retail stores